SPERMATOGENESIS INDICES IN INBRED STRAINS DD/HE AND BALB/CLAC AND THEIR F1 RECIPROCAL CROSSES - M. A. Kleshchev; L. V. Osadchuk; A. V. Osadchuk (Вавиловский журнал генетики и селекции)
We have shown that among 13 inbred mice strains males the DD/He strain has the lowest proportion of mobile sperm and moderate sperm count and proportion of abnormal sperm heads. Males of the BALB/cLac strain have the highest proportion of mobile sperm and abnormal sperm heads, but a moderate sperm count. It is known that Y chromosome genes are important for spermatogenesis. Thus, Y chromosome mutations may be responsible for interstrain differences in spermatogenic parameters. Reciprocal cross can be a useful tool to examine the effect of the Y chromosome on sperm count and the proportions of mobile and morphologically abnormal sperm. The sperm count in DD/He males is higher than in BALB/cLac ones, but both crosses show equal values, exceeding those in the paternal strains. Males of cross BALB/cLac × DD/He have a higher proportion of mobile sperm than males of DD/He × BALB/cLac. The greatest proportion of abnormal sperm heads has been recorded in the BALB/cLac strain. The proportions of abnormal sperm heads in the hybrids were small but little different from each other.